Thermogenic Hydrocarbon Potential on Two Drop Cores Samples from The Surface Geochemical Exploration Program in The Offshores Area of Yamdena Basin, Tanimbar Islands - Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2025)
Seepage of hydrocarbons in near-surface sediments can be categorized into micro and macro seepage, controlled by complex geological, geochemical, and biological processes. Surface geochemical exploration programs have been widely employed to detect and analyze geochemical anomalies on the Earth's surface, which could indicate the presence of subsurface mineral or hydrocarbon deposits. This study aims to characterize two drop core samples extracted from the Yamdena Basin through organic geochemical and isotopic analysis to assess the potential for thermogenic hydrocarbons in the region. A quantitative approach was adopted, utilizing geochemical data, including stable carbon isotope analysis and organic geochemical evaluation through Gas Chromatography (GC) and Gas Chromatography-Mass Spectrometry (GC-MS). The samples analyzed consisted of two piston cores collected during a surface geochemical program conducted by TDI-Brooks International, Inc. This study relies on data from a previous TDI-Brooks International, Inc. survey, with data licensed from TGN-NOPEC Geophysical Company through the Migas Data Repository (MDR) – Pusdatin, focusing on the organic geochemical characterization of drop core samples from offshore Tanimbar Islands. The results indicate that Sample#1 and Sample#2 samples were deposited in a marine setting with varying terrestrial input and exhibited a low maturity level. Geochemical signatures reveal the presence of immature land-plant lipids, suggesting a low potential for thermogenic hydrocarbon generation. The findings highlight the value of surface geochemical exploration programs in mapping hydrocarbon prospects in frontier areas. Furthermore, detailed geochemical analyses can provide insights into the sources and potential of hydrocarbons, aiding in future exploration strategies.